2021
DOI: 10.1111/obr.13228
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to caregivers' responsive feeding behaviour: A systematic review to inform childhood obesity prevention

Abstract: Summary Responsive infant feeding is a critical component of childhood obesity prevention. However, there is little guidance for caregivers on how to do this successfully. The first step to developing an intervention to promote responsive feeding is to systematically identify its barriers and enablers. Searches were conducted in CINAHL, Cochrane Library, Medline, Embase, PubMed, PsycINFO, Maternity, and Infant Care from inception to November 2020. All study designs were included if they reported a barrier or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 72 publications
(392 reference statements)
0
18
0
1
Order By: Relevance
“… Responsive feeding framework. Original framework supported with evidence from Bentley et al ( 7 ); Black and Aboud ( 8 ); National Academies of Sciences, Engineering, and Medicine ( 15 ); Pérez-Escamilla et al ( 2 ); Redsell et al ( 16 ); and Pérez-Escamilla et al( 1 , 2 ) …”
Section: Conceptual Frameworkmentioning
confidence: 65%
“… Responsive feeding framework. Original framework supported with evidence from Bentley et al ( 7 ); Black and Aboud ( 8 ); National Academies of Sciences, Engineering, and Medicine ( 15 ); Pérez-Escamilla et al ( 2 ); Redsell et al ( 16 ); and Pérez-Escamilla et al( 1 , 2 ) …”
Section: Conceptual Frameworkmentioning
confidence: 65%
“…Although a study in New Zealand found that babies following a modified version of BLW had lower satiety responsiveness than a control group, two later observational studies have demonstrated increased satiety responsiveness amongst infants following self-reported BLW, compared to a group following TW. 12,[31][32][33] A further study reported that fully formulafed infants, who were later spoon-fed, were more likely to be overweight than breastfed infants or formula fed infants following BLW. 34 BLW may, therefore, be most beneficial for formula fed infants.…”
Section: Discussionmentioning
confidence: 98%
“…However, no identified studies have evaluated the effectiveness of WIC’s responsive feeding education on feeding outcomes. Even so, a recent review found that responsive feeding skills, knowledge and understanding of feeding and appetite, and education that supports responsive feeding are key enablers of responsive feeding [ 26 ]. In addition, early and repeated exposure to new skills or concepts improve learning outcomes [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%